A COMPARATIVE STUDY OF FOOD SECURITY POLICIES IN DEVELOPING COUNTRIES - Bangkit Ari Sasongko; Ali Rokhman; Denok K Kurniasih (AGUSPATI Research Institute, 2026)
Food resilience has become a strategic policy priority in developing countries due to increasing global challenges, including climate change, supply chain disruptions, economic instability, and public health crises. This study aims to comparatively analyze food resilience policies in Indonesia, the Philippines, and India by examining five key dimensions: food availability, economic and logistics access, nutrition utilization, food system stability, and institutional governance. A purposive literature review method was employed by systematically synthesizing empirical and theoretical studies obtained from Scopus, ScienceDirect, and Google Scholar. The findings indicate that the three countries have adopted different policy approaches based on their institutional capacity and socio-economic contexts, yet they face similar structural challenges. Indonesia has strengthened food diversification and nutrition programs but continues to experience policy fragmentation and unequal regional distribution. The Philippines remains highly vulnerable due to import dependency, geographical constraints, and climate-related disasters that disrupt food accessibility and stability. India has established a comprehensive Public Distribution System (PDS) that improves food access for low-income households; however, administrative inefficiencies, distribution leakages, and nutritional quality remain significant concerns. The comparative analysis demonstrates that food resilience extends beyond increasing agricultural production and requires integrated governance, efficient logistics, transparent institutions, and nutrition-sensitive policies. Furthermore, effective food resilience depends on cross-sectoral coordination, adaptive public administration, and inclusive policy implementation that addresses vulnerable populations. This study contributes to the comparative public policy literature by identifying common challenges and transferable policy lessons among developing countries. It recommends strengthening collaborative governance, institutional integration, digitalized food distribution systems, and climate-adaptive strategies to enhance sustainable and equitable food resilience in Asia.